Waste Minimization in Construction Using Building Information Modeling (BIM) Approach - Jia Yi, Chen; Seow, Ta Wee; Kai Chen, Goh; Shafii, Haryati (Research in Management of Technology and Business, 2021)
Construction waste is no longer a new problem in the construction industry. This is due to the rapid development of the construction industry, which has become a serious problem. Implementing the building information model (BIM) can minimize waste, but BIM is not a popular method for waste minimization in Malaysia. BIM is defined as a digital representation of the physical and functional characteristics of a facility and it is used to integrate data collection, exchange, and visualization during the life cycle of a construction project. This study aims to determine the current implementation of BIM in minimizing construction waste and study the perception of contractors in the challenge of implementing BIM in minimizing waste. The scope area of the study will focus on contractors and construction companies in the Kuala Lumpur area. By the way, this study uses a qualitative method to get the required information and there are 11 respondents will be interviewed. After collecting all the information, analysis of the information collected from the interview will be carried out. The finding of this study, the current implementation of BIM in minimizing waste is still low and the main challenges faced by construction players can be divided into three categories, which are process, people, and technology. In conclusion, the research objectives are achieved and the research study will help to develop the knowledge on the BIM in minimizing waste. So that encourages people to implement BIM in the project and push the Malaysia construction industry into a higher path.